Optimization of the extraction of the p‐menthadienol isomers and aristolone contained in the essential oil from Elyonurus hensii using a 23 full factorial design. Issue 3 (9th February 2017) - Loumouamou, Aubin Nestor; Bikindou, Kévin; Bitemou, Ernest; Chalard, Pierre; Silou, Thomas; Figueredo, Gilles
Abstract: The aim of this study was to optimize the extraction of p ‐menthadienol isomers and aristolone from the essential oil of Elyonurus hensii by hydrodistillation. The study of the seasonal variation in the chemical composition has shown that the plant material has been subject to a natural selection regarding the biosynthesis of the p ‐menthadienol isomers: during periods of water stress, the extracts are rich in cis and trans‐p ‐mentha‐1(7), 8‐dien‐2‐ol and poor in cis and trans‐p ‐mentha‐2, 8‐dien‐1‐ol. Regarding the modeling, eight experiments were carried out by considering three easily interpretable factors (the extraction duration, the residual water content and the state of the division of the plant material). The average yield was 1.33% for the aerial part and 0.74% for the roots. The residual water content is the most important factor, which significantly influences the average yield of the essential oil and the content of the major constituents. Regarding the aerial part, a low residual water content of the plant material varies the essential oil yield (from 0.40% to 2.11%) and the content of cis and trans ‐ p ‐mentha‐2.8‐dien‐1‐ol (from 15.87% to 23.24%). At the root level, the samples that have a very low residual water content provide extracts richer in aristolone. The combined effects of the extraction duration, the state of division, and the residual water content influence greatly the extraction of aristolone (from 36.68% to 54.55%). However, these interactions are more complex and difficult to assess. Abstract : The residual water content is the most important factor which significantly influences the average yield of the essential oil and the content of the major constituents. Regarding the aerial part, a low residual water content of the plant material increases the essential oil yield and the content of cis and trans‐p‐mentha‐2.8‐dien‐1‐ol. To the roots, the samples which have a very low residual water content should provide extracts richer in aristolone.